Communicative Practices of Migrants in the Transnational Space - Ledeneva, Viktoria (KnE Social Sciences, 2021)
Th article is devoted to the analysis of intercultural global interaction in the format of transnational communication networks that migrants form, moving from the country of origin to the country of reception. The purpose of the article is to describe and analyze the phenomenon of the reproduction of ethnic identity in transnational spaces, where migrants mainly from Central Asian countries form new multicultural models of behavior based on their own cultural patterns and identities. The article emphasizes that cultural systems involve diverging, but overlapping of migrant groups’ patterns of behavior. Thus, the problem situation is determined by ignorance of the features of everyday communication and behavioral patterns adopted in different groups of migrants. The author analyzes various adaptation strategies of migrants, emphasizing that the choice of a particular strategy depends on the motivation of the migrant. The problem of migrant groups’ integration is identified in the article as state policy aimed not only at working with migrants in order to successfully include them in the host community, but also at interacting with the host community itself and the local population. Organizational, integration and financial resources spent on working with migrants will not be effectively used if we do not take into account the differences between ethnic migrant groups, which are identified, including in the particularities of communication practices and the construction of communicative transnational spaces. The research methodology includes the main components of a transnational approach, in the framework of which it is noted that the concept of “international migration”, which involves crossing borders, is losing its relevance. migrants more and more differ in socio-cultural characteristics, are oriented towards life in two or more societies, the development of transnational communities and the corresponding consciousness. In transnational communications, a special role belongs to diaspora communities. The main conclusion of the article is that the concept of transnational and translocal migration sets a new globalist perspective. The locality is being replaced by the process of translocality, and transmigrants belong to several localities at the same time and are included in more than one community. Keywords: transnational migrations, adaptation strategies, communication practices, transnational space The publication has been prepared with the support of the «RUDN University Program 5-100»